Les Allemagnes et la division Est-Ouest : Une ambivalence politique - Létourneau, Paul (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1985)
This article is about the role of international bureaucracies in the determination of the general policies of international organizations. In this paper it is argued that in general international organizations' Secretariats generally do wield, considerable power over the definition of the institutions' strategies, i.e. those activities, priorities and projects which taken together make up the program of the institution for a given period. Indeed, the international bureaucrats exercise tremendous control over the content of the program. This is so because international organizations have special functions in the world System. They must see to it that, certain states of affairs prevail in the world over the long run. It is, therefore, no surprise that the programs' content be more or less shielded from conjonctural fluctuations. The article then proceeds to test these hypotheses on a concrete case: the analysis of the processus through which Unesco's program goes before becoming the official policy of the organization.